On Health Care Sectore, What External Environment that Important? : A Review Literature - Noor SyamSidiq Himawan; Nur Wening (Institute of Medico-legal Publications Pvt Ltd, 2021)
This Paper is a literature review related to various studies that discuss macro environmental analysis(political, economic, socio-cultural and technological) in the field of health care. The purpose of this studyis to explore and connect theories from various studies related to macro business environment factors thatare important in the field of health care, how much research is related and what are the opportunities forfuture research. This paper identifies 21 articles that discuss the analysis of the business environment inthe health care sector. In this study, the criteria for selecting literature were applied, namely the selectedliterature must be in the form of articles not handbooks, in English, discussing business environmentalanalysis, especially in the field of health services and published for a maximum of the last 10 years. Theresearch related to political factors was 31.25%, economic factors 18.75%, socio-cultural factors 18.75%and technological factors 31.25%. Research related to environmental analysis (political, economic, socioculturaland technological factors) in the health sector is still very minimal, especially in the economic andsocio-cultural sectors so that this can actually become an opportunity in developing research on the businessenvironment in the health sector.